2013
DOI: 10.1186/1752-1505-7-4
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of gender inequitable norms and gender-based violence in South Sudan: a community-based participatory research approach

Abstract: BackgroundFollowing decades of conflict, South Sudan gained independence from Sudan in 2011. Prolonged conflict, which included gender-based violence (GBV), exacerbated gender disparities. This study aimed to assess attitudes towards gender inequitable norms related to GBV and to estimate the frequency of GBV in sampled communities of South Sudan.MethodsApplying a community-based participatory research approach, 680 adult male and female household respondents were interviewed in seven sites within South Sudan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…Informants linked a high risk of exposure to IPV among women to the societal patriarchal structure and unequal gender power relations. This link is confirmed by studies in other Sub-Saharan Africa countries [33, 34] and in Asia/the Pacific [35]. At a community level, the present study revealed how the war has contributed to a ‘violence-permitting’ climate, in addition to other risk factors such as khat use and poverty [36].…”
Section: Discussionsupporting
confidence: 86%
“…Informants linked a high risk of exposure to IPV among women to the societal patriarchal structure and unequal gender power relations. This link is confirmed by studies in other Sub-Saharan Africa countries [33, 34] and in Asia/the Pacific [35]. At a community level, the present study revealed how the war has contributed to a ‘violence-permitting’ climate, in addition to other risk factors such as khat use and poverty [36].…”
Section: Discussionsupporting
confidence: 86%
“…The Fertit, like the other South Sudanese ethnic groups, are patriarchal; men have the power to decide on all aspects of the family and in society at large, and women's position is subordinate to men (20–23). The Fertit consider the notion of being respectable, and worthy, of great importance; boys and men count, whereas women do not.…”
Section: Unequal Status and Power Relations Between The Sexesmentioning
confidence: 99%
“…Unlike the Dinka and the Nuer, who are pastoralists, the Fertit are predominantly agriculturist people involved in subsistence farming. The Fertit, like all other South Sudanese ethnic groups, are patriarchal; men have the power to decide on all aspects of the family and in society at large, and women’s position is subordinate to men [911]. Edwards [12] argues that a range of societal, historical and political processes have led to a situation where gender inequalities in South Sudanese society have become entrenched and disadvantage women in social, economic and political realms alike.…”
Section: Introductionmentioning
confidence: 99%